THE ECONOMIC PARADIGM OF KORAN IN COUNTERING RADICALISM - Gusnanda, Gusnanda (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
This paper examines the Quranic paradigm in solving the problem of radicalism that is developing in the world today. One of the root causes of radicalism is poverty and economic inequality. Meanwhile, religion is only a trigger. The results of this research show that poverty, inequality and injustice are the main factors in the birth of radicalism. Islam is a way of salvation and peace that never teaches radicalism to its adherents. Efforts to break the chain of radicalism must be done with an economic approach. Considering that many acts of radicalism come from within Muslims, it is necessary to strengthen the economy among Muslims. This action is an effort to stem and stop acts of terror and radicalism that are mostly carried out by Muslim groups. Some of these efforts include optimizing the potential of philanthropy to improve the circulation of the ummah's internal finances.